Preparation and Characterization of Gallium Doped ZnO/Epoxy Composite as Thermal-Insulating Coating - Mei, Shi-Gang; Wang, Jian-Lei; Yong, Kang; Zhang, Guang-Lei; Li, Yuan-Qing (Asian Journal of Chemistry, 2012)
In this article, transparent gallium doped zinc oxide (GZO)/epoxy composites, as glass thermal insulation coating, were prepared by incorporating gallium doped zinc oxide nanoparticles into a transparent epoxy matrix. The effects of gallium doped zinc oxide content on the optical and thermal insulation property of gallium doped zinc oxide/epoxy coating were studied. The results reveal that the gallium doped zinc oxide/epoxy composite coating with 0.5 wt % gallium doped zinc oxide possesses excellent optical properties, i.e., visible light transmittance above 45 % and shading coefficient of 0.43 are simultaneously achieved. In addition, the large stable temperature difference between chamber with gallium doped zinc oxide/epoxy coated glasses and common glass indicates that the prepared gallium doped zinc oxide/epoxy coating has excellent thermal insulation property.